Pengaruh Konsumsi Mix Jus Seledri dan Nanas Terhadap Penurunan Tekanan Darah Lansia Hipertensi - Elmania Ngoma Nala; Wira Daramatasia; Muntaha . (STIKES Widyagama Husada, 2026)
AbstractAs people age, they tend to experience health problems due to degenerative processes or other external factors. One of the common health problems found in the elderly is hypertension, a condition of increased blood pressure that can trigger serious complications in the cardiovascular system. Hypertension treatment does not only rely on pharmacological therapy but also requires a non-pharmacological approach, one of which is through the consumption of foods or drinks containing bioactive compounds. Celery is known to contain phytochemicals such as apigenin, which is a vasodilator, while pineapple is rich in potassium, which helps maintain blood pressure balance. This study aims to determine the effect of consuming a mixture of celery juice and pineapple juice on reducing blood pressure in elderly hypertensive patients at the Mojolangu Health Centre. This study used a quasi-experimental design with a pretest-posttest control group approach. The population consisted of 51 elderly hypertensive patients, and 34 respondents were selected through accidental sampling techniques. Data were collected using observation sheets and digital tensiometers, which were then analysed using the Wilcoxon and Mann-Whitney U tests. The results of the Wilcoxon test showed a significant decrease in systolic and diastolic blood pressure in the treatment group (p = 0.000), while the control group did not show significant changes. The Mann-Whitney U test also showed a significant difference between the two groups (p=0.000). The conclusion of this study is that the consumption of a mixture of celery juice and pineapple juice significantly affects the decrease in blood pressure in elderly people with hypertension. Keywords: Celery Juice; Pineapple Juice; Blood Pressure; Hypertension..